ANALISIS RELATIONSHIP MARKETING TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER RETENTION PADA NASABAH BANK MUAMALAT CABANG BANGKINANG-KABUPATEN KAMPAR - Diantara, Litra (Jurnal Tepak Manajemen Bisnis, 2015)
Analisis Relationship Marketing And Customer Satisfaction to Customer Retention On PT. Muamalat Bank Bangkinangs Branch, under guidance Samsir and Sri Restuti. This research has a purpose to test relationship marketings influence, customer satisfaction to customer retention. That variable purpose in consideration former research results, same under consideration variable relationship marketing. That variable purpose get to determine excesses and lack for on PT. Muamalat Bank Bangkinangs Branch.This observational sample is client. PT Muamalat Bank Bangkinangs Branch, to amount to 112 person. Structural Equation is Modelling (SEM) one that carried on by AMOS software, utilized for analisis data, analisis result points out that relationship marketing having for positive and signifikan via customer satisfaction to customer retention and customer satisfaction having for positive and signifikan to customer retention.Result observationaling to betoken that to increase customer retention, one that makes an acquisition be of important from emulation among bank that is at Bangkinang. PT. Muamalat Bank Bangkinangs Branch needs to notice factors as relationship marketing on conflict handling point and communication, all that has improved again to be able to reach for client point, and top was winked by client, since that factor is evident high regard its lows client satisfaction that regard defensive client or customer retention. Theoretical implication and tipses for observational approaching also untied at the end in this research.Keywords: Relationship Marketing, Customer Satisfaction, Customer Retention